Highly Enhanced Third-Harmonic Generation in 2D Perovskites at Excitonic Resonances. - Abdelwahab,I; Grinblat,G; Leng,K; Li,Y; Chi,X; Rusydi,A; Maier,SA; Loh,KP (ACS Nano, 2018)
Two-dimensional hybrid organic-inorganic Ruddlesden-Popper perovskites (RPPs) have attracted considerable attention due to their rich photonic and optoelectronic properties. The natural multi-quantum-well structure of 2D RPPs has been predicted to exhibit a large third-order nonlinearity. However, nonlinear optical studies on 2D RPPs have previously been conducted only on bulk polycrystalline samples, in which only weak third-harmonic generation (THG) has been observed. Here, we perform parametric nonlinear optical characterization of 2D perovskite nanosheets mechanically exfoliated from four different lead halide RPP single crystals, from which we observe ultrastrong THG with a maximum effective third-order susceptibility (χ(3)) of 1.12 × 10-17 m2 V-2. A maximum conversion efficiency of 0.006% is attained, which is more than 5 orders of magnitude higher than previously reported values for 2D materials. The THG emission is resonantly enhanced at the excitonic band gap energy of the 2D RPP crystals and can be tuned from violet to red by selecting the RPP homologue with the requisite resonance. Due to signal depletion effects and phase-matching conditions, the strongest nonlinear response is achieved for thicknesses less than 100 nm.